2012
DOI: 10.1074/jbc.m111.336487
|View full text |Cite
|
Sign up to set email alerts
|

C-terminal Di-arginine Motif of Cdc42 Protein Is Essential for Binding to Phosphatidylinositol 4,5-Bisphosphate-containing Membranes and Inducing Cellular Transformation

Abstract: Background:We have examined the role of the polybasic domain of Cdc42 in its membrane association and transforming capability. Results: We show that a di-arginine motif within Cdc42 is essential for binding to PIP 2 -containing membranes and cellular transformation.Conclusion: These findings demonstrate that Cdc42 binds to specific membrane sites to trigger oncogenic transformation. Significance: These findings shed new light on how Cdc42 initiates transforming signals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 47 publications
2
44
0
2
Order By: Relevance
“…This finding is consistent with previous studies in Rac1GTPases, which provide evidence that the membrane translocation can occur independent of GEF activation, e.g., caRac1 exhibiting polarized distribution in lamellipodia (50), and Rac1 membrane association occurring at the boundaries of rafts and lipid rafts followed by diffusion into the rafts for GEF-mediated activation (56). Similarly, in other RhoGTPases, like cdc42, the critical role of protein−lipid interactions (via the polybasic domain) in modulating cell growth and transformation has also been demonstrated (57). The emergence of the sptPALM technique has made particle tracking in live cells relatively easy to implement (18,19,22).…”
Section: Discussionmentioning
confidence: 89%
“…This finding is consistent with previous studies in Rac1GTPases, which provide evidence that the membrane translocation can occur independent of GEF activation, e.g., caRac1 exhibiting polarized distribution in lamellipodia (50), and Rac1 membrane association occurring at the boundaries of rafts and lipid rafts followed by diffusion into the rafts for GEF-mediated activation (56). Similarly, in other RhoGTPases, like cdc42, the critical role of protein−lipid interactions (via the polybasic domain) in modulating cell growth and transformation has also been demonstrated (57). The emergence of the sptPALM technique has made particle tracking in live cells relatively easy to implement (18,19,22).…”
Section: Discussionmentioning
confidence: 89%
“…Moreover, isoprenylated Cdc42 was found to bind directly and tightly to liposomes as long as they contain PI(4,5)P 2 (ref. 37).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on Ras, another prenylated protein, revealed that prenylation alone is not sufficient for stable plasma membrane association, and that additional palmitoylation (in the cases of N-Ras, H-Ras, and K-RasA) or positively charged residues (in the case of K-RasB) is required [30]. In the plasma membrane, negatively charged phospholipids such as phosphoinositides, phosphatidylinositol, and phosphatidylserine are asymmetrically enriched in the inner leaflets [36] and interact with positively charged residues [31]. We demonstrated here that ALDH3B1 is palmitoylated at Cys462 and Cys463 ( Figure 3D) and that the positively charged residues Arg462 and Arg463 are important for the plasma membrane localization of ALDH3B3 ( Figure 5B).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that clusters of positively charged residues near prenylation sites are important for the plasma membrane localization of K-RasB and Cdc42 [30,31]. Therefore, to examine the role of Arg residues in the plasma membrane localization of ALDH3B3, we created a double Ala-substituted mutant (R462/463A), in which both the Arg462 and Arg463 residues were substituted with Ala residues.…”
Section: The C-terminal Regions Of Aldh3b2 and Aldh3b3 Determine Theimentioning
confidence: 99%